PHARMACOKINETIC STUDY OF ENROFLOXACIN IN TIANFU GEESE - F. Shi; H. Tang; W. Xie; A. Anees; Z. Yang; X. Zhang (Journal of Animal and Plant Sciences, 2014)
The pharmacokinetic behavior of enrofloxacin (EF) was investigated in geese after oral (p.o.) and intravenous (i.v.) administrations of a single dose of 20 mg/kg body weight. Plasma concentrations of EF and its active metabolite, ciprofloxacin, were determined by high performance liquid chromatography fluorescence method. Plasma concentrations versus time were analyzed by non-compartmental method. The elimination half-life and area under drug concentration-time curve from zero to infinity of EF after i.v. administration were 3.32 ± 0.43 h and 45.73 ± 5.74 mg/L·h, respectively. After p.o. administration, EF was absorbed fast and the maximum plasma concentration of 3.86 ± 0.36 mg/L reached at 2.14 ± 1.10 h. The concentration-time profile of EF showed a double peak-shaped curve, indicating the possibility of enterohepatic recirculation of EF in geese. The bioavailability for EF after p.o. administration was 78.09 ± 25.76%. Seldom ciprofloxacin was detected in the plasma both after i.v. and p.o. administrations, indicating low transformation rate from EF to ciprofloxacin in geese. Taking into account the efficacy indices obtained, a single p.o. dose of 20 mg/kg of EF would be adequate for treating infections caused by highly susceptible bacteria in geese.
Keywords: pharmacokinetics; enrofloxacin; geese; intravenous administration; oral administration